Upaya Peningkatan Keberlanjutan Akseptor KB Melalui Aplikasi Pengingat KB di Kampung KB Kota Padang - Erwani; Dewi Susanti; Elda Yusefni; Alsri Windra Doni; Metri Lidya; Aprizal Ponda (CV. CENDIKIA JENIUS INDONESIA, 2024)
(The incidence of unmet need for family planning in Indonesia increases from year to year. In West Sumatra in 2017 it was 18.54%. The third highest incidence of unmet need in Padang City was in Bungus District (29.62%), Nanggalo (22, 47). %) and Lubuk Kilangan 28.22%). The aim of this activity is to provide a reminder application for re-controls and complaints from acceptors regarding the contraception they are using and to cover if the acceptor wants to change to another type of contraception. Appropriate technology is a family planning reminder application for acceptors. The implementation method uses 2 methods, namely the participatory planning method and the practical method. The results of this activity were able to increase the knowledge of family planning cadres about the concept of unmet need for family planning and the use of the family planning reminder application by 81.7% after training. 100% of family planning cadres were able to use the family planning reminder application and were able to socialize it to family planning acceptors. The conclusion of this activity is that there is an increase in family planning cadres' knowledge about the concept of unmet need and in using the family planning reminder application. It is recommended to stakeholders to ensure the continued use of the family planning reminder application.